2017
DOI: 10.1016/j.jaut.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 and -15 maintain pathogenic memory Th17 cells in autoimmunity

Abstract: Th17 cells are principal mediators of many autoimmune conditions. Recently, memory Th17 cells have been revealed as crucial in mediating the chronicity of various refractory autoimmune disorders; however, the underlying mechanisms maintaining memory Th17 cells have remained elusive. Here, using a preclinical model of ocular autoimmune disease we show that both IL-7 and IL-15 are critical for maintaining pathogenic memory Th17 cells. Neutralization of these cytokines leads to substantial reduction of memory Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
0
42
0
1
Order By: Relevance
“…TSP-1 mRNA has been identified in corneal epithelium and stroma, and the protein has been immunolocalized in corneal tissue [12, 33]. Using a validated murine model of DED, our study demonstrates a progressive increase in TSP-1 mRNA expression levels over time in mice exposed to desiccating stress [34, 35]. We hypothesized that enhanced production of TSP-1 by the corneal epithelium may be a compensatory mechanism that curbs the vigor of the immune response in DED, thus protecting the integrity of the ocular surface.…”
Section: Discussionmentioning
confidence: 92%
“…TSP-1 mRNA has been identified in corneal epithelium and stroma, and the protein has been immunolocalized in corneal tissue [12, 33]. Using a validated murine model of DED, our study demonstrates a progressive increase in TSP-1 mRNA expression levels over time in mice exposed to desiccating stress [34, 35]. We hypothesized that enhanced production of TSP-1 by the corneal epithelium may be a compensatory mechanism that curbs the vigor of the immune response in DED, thus protecting the integrity of the ocular surface.…”
Section: Discussionmentioning
confidence: 92%
“…Epithelial cells, upon TLR stimulation, also produce T-cell homeostatic cytokines, like IL-7, that is an important mediator of T-cell activation (51), IFN-gamma-mediated Th1 response (52) and maintenance of pathogenic Th17 cells (53). These infiltrating CD4+ T cells (Th1 and Th17) show an activated phenotype and release pro-inflammatory cytokines like IFNγ (Type II IFN), IL-17 and IL-6.…”
Section: Pathogenesismentioning
confidence: 99%
“…In a mouse model of chronic DED, Chen et al demonstrated that the persistent inflammation seen in the chronic phase of the disease is mediated by an effector memory Th17 population [78]. IL-7 and IL-15 have been shown to be critical in maintaining this pathogenic subset, and in vivo blockade of these signalling pathways prevents the development of chronic DED [80]. Th17 immunity in DED is also dependent on the expression of C-C chemokine receptor (CCR)-7 by APCs, which directs APC migration towards lymphoid tissue, across a C-C motif chemokine ligand 21 (CCL21) chemotactic gradient [81].…”
Section: Autoimmunity At the Ocular Surfacementioning
confidence: 99%